PERANCANGAN SISTEM E-LAUNDRY BERBASIS WEBSITE PADA IBI LAUNDRY DENGAN METODE EXTREME PROGRAMING - Ahmad Suryana; Dede Supiyan (Journal of Research and Publication Innovation, 2025)
IBI Laundry is a laundry service business that still relies on manual systems for order processing and customer data management, resulting in various issues such as disorganized data, risk of information loss, and inefficient service delivery. Therefore, a web-based system is needed to support faster, more accurate, and integrated operations. This research aims to design a web-based E-Laundry system to assist IBI Laundry in managing transactions and customer data digitally. The development method used in this study is Extreme Programming (XP), which emphasizes team collaboration, iterative development, and rapid user feedback. The stages in this method include planning, design, coding, and testing. The result of this research is a web-based E-Laundry system with features such as laundry status tracking, customer data management, and transaction reporting. The implementation of this system improves service efficiency and organization, as well as enhances customer satisfaction with IBI Laundry's services. This study is expected to be an innovative solution for the digitalization of laundry services and serve as a reference for similar system development projects.